Impact of Urban-Rural Resident Basic Medical Insurance integration on individual social fairness perceptions: evidence from rural China - Liu, Dandan; Chu, Yifei (Frontiers in Public Health, 2024)
Background Achieving universal health insurance coverage has become a fundamental policy for improving the accessibility and equity of healthcare services. China's Urban-Rural Resident Basic Medical Insurance (URRBMI) is a crucial component of the social security system, aimed at promoting social equity and enhancing public welfare. However, the effectiveness of this policy in improving rural residents' social fairness perceptions (SFP) remains to be tested. Objective To examine the impact of the urban-rural resident basic medical insurance (URRBMI) on rural residents' social fairness perception (SFP) in China. Methods and samples The study utilizes city-level and national micro-survey (CGSS) datasets, applying a time-varying difference-in-difference (DID) approach to analyze the equity effects of URRBMI. Excluding urban samples, the final dataset consists of 20,800 rural respondents from 2010, 2011, 2013, and 2015, covering 89 cities. Results Key findings reveal that URRBMI has a significant negative effect on SFP. The impact varies depending on the integration model and intensifies over time. Additionally, the negative effect shows heterogeneity based on income, age, health, and region. Conclusion This study highlights the complexities and impacts of integrating China's urban and rural healthcare systems. It provides a detailed understanding of the role of URRBMI in rural China, emphasizing the need for targeted approaches to improve rural residents' perceptions of social fairness. The research offers specific policy recommendations, such as establishing differentiated contribution standards, implementing welfare policies favoring rural residents, and adopting varied reimbursement rates for different diseases.